1998
DOI: 10.1897/1551-5028(1998)017<1490:aohaha>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Halogenated Aromatic Hydrocarbons and Activities of Cytochrome P450 and Glutathione S-Transferase in Crabs (Eriocheir Japonicus) From Japanese Rivers

Abstract: Abstract-The hepatopancreases of freshwater crabs (Eriocheir japonicus) collected from three Japanese rivers (Barato, Shiribetsu, and Tone) were analyzed for planar halogenated aromatic hydrocarbons (HAHs), including polychlorinated dibenzo-p-dioxins (PCDDs), dibenzofurans (PCDFs), and coplanar polychlorinated biphenyls (PCBs). The hepatic glutathione S-transferase (GST)-dependent enzyme activities in the crab hepatopancreas were also measured to examine their potential as biomarkers for the contaminants. Crab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(55 reference statements)
0
4
0
1
Order By: Relevance
“…Hydrophobic pollutants, such as organochlorine compounds and polycyclic aromatic hydrocarbons, can readily accumulate in the tissues of crustaceans (Ishizuka et al 1998;Menone et al 2000;Eickhoff et al 2003). It conjugates potentially harmful electrophilic substances with endogenous reduced glutathione to protect other nucleophilic molecules, such as proteins and nucleic acids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophobic pollutants, such as organochlorine compounds and polycyclic aromatic hydrocarbons, can readily accumulate in the tissues of crustaceans (Ishizuka et al 1998;Menone et al 2000;Eickhoff et al 2003). It conjugates potentially harmful electrophilic substances with endogenous reduced glutathione to protect other nucleophilic molecules, such as proteins and nucleic acids.…”
mentioning
confidence: 99%
“…Hydrophobic pollutants, such as organochlorine compounds and polycyclic aromatic hydrocarbons, can readily accumulate in the tissues of crustaceans (Ishizuka et al 1998;Menone et al 2000;Eickhoff et al 2003). The correlation between enzymatic activity and contaminant accumulation and the induction of GST activity by organic contaminants have led to the suggestion of GST activity in the hepatopancreas of crustaceans as a biomarker for organic pollution (Ishizuka et al 1998;Gowland et al 2002;Arun et al 2006). Ishizuka et al (1998) reported the correlation between GST activity and the accumulation of organochlorines in the hepatopancreas of the freshwater crab, Eriocheir japonicus.…”
mentioning
confidence: 99%
“…The same study reported 1271 to 15 792 PCDD/DFs from sediments, 377 in Ono River, 1608 from paddy field around KUL and reference soil 2171 from Tokyo urban on pg/g dry weight basis. Crabs collected from Tone River had 1100 pg/g fat weight PCDD/DFs, 3000 pg/g co-planar PCBs and 94.7 pg/g TEQs [20]. As indicated before, Koise River, Ono River, Sakura River and Tone River downstream into the KUL and expected to deposit larger amount of toxic contaminants in to the KUL.…”
Section: Pcdds/pcdfsmentioning
confidence: 55%
“…However, this does not rule out the possibility of drug induction in invertebrates. That is what a Japanese team [47] has shown in crabs by measuring glutathione S-transferase activity in hepatopancreas.…”
Section: Biological Effects and The Concept Of 2378-tcdd Toxic Equmentioning
confidence: 62%